Ecotourism Development Potential Based on Environmental Comfort in Gunung Walat University Forest Area, Sukabumi, Indonesia - Agustian, Rozi; Rusdiana, Omo; Hadianto, Adi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Gunung Walat University Forest (GWUF) in Sukabumi, West Java, serves as a centre for training, education, and research in forestry. This research analyses the environmental comfort of GWUF, focusing on thermal comfort, visual aesthetics, and visitor perceptions related to their suitability in conducting ecotourism development to increase GWUF income in realizing sustainable forest management. Data was collected from November 2023 to February 2024 at three locations in the GWUF by measuring air temperature and humidity. Interviews were conducted with respondents experienced in landscape assessment to evaluate the aesthetic level of 10 objects in GWUF, and interviews with visitors on aspects of GWUF management and presence. The Thermal Humidity Index (THI), Scenic Beauty Estimation (SBE), and Likert scale analysis were also used. The results showed that the GWUF area was in a comfortable thermal condition. The value varied and became a new attraction, one of which was the beauty of the GWUF cave. Overall, visitors rated the air quality and natural beauty positively; however, there are some points to note regarding the availability of facilities and the accessibility of the site, highlighting areas for improvement in management.